Implementation of the snowball throwing method in PAI subjects to improve student learning outcomes - Ambarsari, Siti Nuartika; Muharom, Fauzi; Supriyanto, Supriyanto (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Implementation of The Snowball Trowing Method In Subjects of Islamic Religious Education In Increasing Student Learning Outcomes. This study aims to (1) apply the snowball throwing learning model in Islamic Religious Education learning. (2) to determine student learning outcomes after applying the snowball throwing learning model, especially in learning Islamic Religious Education. (3) to improve student learning outcomes through the snowball rolling learning model. This research is expected to be useful for teachers, schools and future researchers. For teachers, hopefully the results of this research can improve their teaching skills, especially in terms of innovative learning models. The methodology in this research is field research obtained through classrooms or what is called classroom action research (CAR). This research method uses two cycles. The first cycle consists of the planning stage (planning), the implementation action stage (action), the observation stage (observation), and the reflection stage. At the reflection stage of the first cycle, student learning outcomes were analyzed to correct deficiencies, then continued in the second cycle. . The results showed that the learning outcomes of Class IV after using the Snowball Throwing model were higher than those who did not use it